2004
DOI: 10.1109/joe.2004.833216
|View full text |Cite
|
Sign up to set email alerts
|

Review of Experimental Work in Biomimetic Foils

Abstract: Abstract-Significant progress has been made in understanding some of the basic mechanisms of force production and flow manipulation in oscillating foils for underwater use. Biomimetic observations, however, show that there is a lot more to be learned, since many of the functions and details of fish fins remain unexplored.This review focuses primarily on experimental studies on some of the, at least partially understood, mechanisms, which include 1) the formation of streets of vortices around and behind two-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
198
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(208 citation statements)
references
References 124 publications
8
198
2
Order By: Relevance
“…Any new breakthrough in the mechanism will bring new inspiration to the developments of biomimetic propulsors. Therefore, to explore the mechanism, scholars are spending considerable efforts to reveal the essence of the problems with different research methods [3][4][5][6][7][8][9][10]. Among the methods, numerical simulation method has gained growing attention because of its advantages of low input, high efficiency and simple post-processing.…”
Section: Introductionmentioning
confidence: 99%
“…Any new breakthrough in the mechanism will bring new inspiration to the developments of biomimetic propulsors. Therefore, to explore the mechanism, scholars are spending considerable efforts to reveal the essence of the problems with different research methods [3][4][5][6][7][8][9][10]. Among the methods, numerical simulation method has gained growing attention because of its advantages of low input, high efficiency and simple post-processing.…”
Section: Introductionmentioning
confidence: 99%
“…Note that this value is based on the reference velocity U ref , as it enters equation (1). To obtain the Reynolds number based on the wing velocity, this value should be corrected by a factor proportional to the stroke frequency.…”
Section: A Single Wing Sectionmentioning
confidence: 99%
“…In the twodimensional approximation, shown in Fig. 1(b), this is equivalent to prescribing a heave motion y le (t) and a pitch motion α(t) (see, e.g., [1]). However, if the wing is flexible and clamped at the leading edge, the effective angle of incidence varies passively due to the action of inertial and aerodynamic forces (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is also confirmed that the CPG-based swimming control exhibits better dynamic invariability in preserving rhythm than the conventional body wave method. Robotic fish, inspired by fish in nature, have received increasing attention in recent years because of potential aquatic-related applications such as exploration, surveillance, transportation, and mobile sensing [1][2][3][4][5][6][7]. Many scientists and engineers have carried out studies on robotic fish, focusing not only on the hydrodynamics mechanism and bio-inspired practice of fishlike swimming, but also on motion planning, control, and optimization of the fishlike robots [2].…”
mentioning
confidence: 99%